The Usborne book of famous artists - Brocklehurst, Ruth.; Adler, Kathleen; Beech, Mark, 1971-; Dickins, Rosie; Wheatley, Abigail, 1974- (London : Usborne ; Tulsa, Okla. : EDC Pub., 2011)
Introduces the lives and works of thirty-five famous artists, illustrated with reproductions of the artists' works, with timelines that provide the key dates in each artist's life.
Includes index.
7.2
3-6.
3-6
Keywords: Artists -- Biography -- Juvenile literature; Artists; Artists -- Biography